Ventilator - associated pneumonia in intensive care units And physician - nurse relationship role - Asgar Mobasher Amini; Baghaie Lakeh; Asgari; kazemnejad Leili (Guilan University of Medical Sciences, 2016)
Introduction: Ventilator-associated pneumonia is one of important factors of morbidity and mortality in critical care units, associated with hospitalization day s and increased cost of treatment. Thus prevention through identifying related factors must be highly recommended Objective: This study is conducted by the aim of determining the nurses understanding of physician-nurse relationship with Ventilator – associated pneumonia reports in critical care units of Guilan University of Medical Sciences Methods: This cross-sectional –analytic study conducted by selecting 101 nurses from 7 critical care units of Guilan province with determined characters by census method. Data were gathered by a 3-part tool consisting demographic data and ventilator associated pneumonia recording data for 3 months before sampling and standard Practice Environment Scale of the Nurses Work Index (physician-nurse relationship) by interview. Mean of reported pneumonia frequency classified in 3 groups of none, 1-5 cases and more than 5 cases. Mean of physician-nurse relationship classified in 2 groups of desirable and undesirable. Data were analyzed using descriptive statistics and analytic tests (chi-square). Results:The findings showed that majority of samples (62/7%) 1-5 were related to ventilator associated pneumonia. This variable had significant relation with years of employments in samples (p=0.004). Mean score of 72.5 percent of samples in physician-nurse relationship was in favorable level with no significant relationship with personal variables exept the nurses` employment status (p=0.035). Finally, χ2 statistical test showed significant relationship between favorable perceived physician – nurse communication and lower Ventilator-associated pneumonia (p=0.01). Conclusion: Significant relation between ventilator associated pneumonia and physician-nurse communication in this survey indicated that possibility of prevention of pneumonia by improving nurse-physicians relationship and collaboration quality